Zoonotic parasites in wild animals such as carnivores and primates that are traded illegally in Brazil - Victor Fernando, Victor Fernando; do Nascimento Ramos, Rafael Antonio; Giannelli, Alessio; Cerqueira Schettino, Sofia; Beal Galina, André; Cardoso Pessoa de Oliveira, Jéssica; Oliveira Meira-Santos, Patrícia; Alves, Leucio Camara (Brazilian Journal of Veterinary Medicine, 2021)
Brazil accounts for around 20% of all animal species, but these are constantly threatened by illegal anthropic activities. Unfortunately, animal dealers are totally unaware of the sanitary risks among wild animals, or that occurrences of parasites in these animals are bioindicators for their current sanitary status within the ecosystem in which they live. This status is an important parameter with regard to assessing the spreading of pathogens. Therefore, the aim of this study was to perform a survey of zoonotic parasites in carnivores and non-human primates that are illegally traded in Brazil. Between June 2016 and July 2017, 43 wild animals (20 carnivores and 23 non-human primates) were presented at the Wild Animal Screening Center of Sergipe (CETAS/SE). Fecal and blood samples were obtained and analyzed to detect occurrences of pathogens of medical and veterinary importance, such as Cryptosporidium spp., Giardia spp., Dirofilaria immitis, Leishmania infantum, Leishmania braziliensis, Toxoplasma gondii, Trypanosoma cruzi and gastrointestinal helminths. Out of all the animals analyzed, 55.8% (24/43) were found to be positive for at least one parasite species, i.e. 41.7% and 58.3% of the carnivores and non-human primates, respectively. However, all the animals were negative for D. immitis, L. braziliensis and T. cruzi. These findings demonstrate that illegally traded wild animals may represent a risk to public health because of absence of sanitary control during their transportation. Therefore, preventive measures might be employed to avoid infection of these animals and people in close contact with them.